STRATEGY OF ISLAMIC COLLEGE (STAI) AL-HIDAYAH BOGOR IN IMPROVING STUDENTS' AL-QUR'AN READING ABILITY - Maya, Rahendra; Sarbini, M; Muharam, Aditya (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Objective: This study analyzes the strategy of the Al-Hidayah Bogor Islamic Religious College (STAI) in improving students' Qur'an reading ability, especially from a general education background. Methods: The research used a qualitative approach with case studies, collecting data through observation, interviews, and literature studies. Results: The results of the study show that the main strategy of STAI Al-Hidayah is the establishment of the Institute for Da'wah, Tahfizh, and Arabic Language (LDTBA) and making the Tahfizh course a mandatory course for the first two semesters for all students. In this course, students are taught tajwîd and tahsîn to improve their ability to read the Qur'an. In addition, LDTBA programs and lecturers' creativity also support the improvement of Qur'anic reading skills. Conclusion: The positive impact can be seen from the Tahfizh exam which shows that the majority of students graduate with good reading of the Qur'an, no longer stuttering or spelling like at the beginning of lectures.